Identification of learning habits of grade IV students of the elementary school - Hanita Yulinda; Fabrina Dafit (Himpunan Pengembang Kurikulum Indonesia, 2025)
Effective learning strategies can lead to high-quality education. This study investigates the learning patterns of outstanding students at SDN 020 Tanjung Harapan, Kampar Regency, using a qualitative descriptive research design. The research subjects consisted of students in grades 1, 2, and 3, homeroom teachers, and parents of children with special needs. Data were collected through interviews and observations, and analyzed through three stages: data reduction, data display, and conclusion or verification. The research findings reveal that high-achieving students tend to demonstrate positive study habits, including organizing and creating study plans, regularly attending classes, reviewing materials, managing time efficiently, maintaining focus, and applying discipline in their studies. These learning strategies are practiced both at school and at home, enabling students to manage academic stress effectively and sustain high performance. Furthermore, these findings are expected to motivate underachieving students to adopt similar study patterns, ultimately leading to improved academic outcomes and personal development. Abstrak Strategi pembelajaran yang efektif dapat menghasilkan pendidikan berkualitas tinggi. Penelitian ini bertujuan untuk mengkaji pola belajar siswa berprestasi di SDN 020 Tanjung Harapan, Kabupaten Kampar, dengan menggunakan desain penelitian deskriptif kualitatif. Subjek penelitian terdiri dari siswa kelas 1, 2, dan 3, wali kelas, serta orang tua dari anak berkebutuhan khusus. Pengumpulan data dilakukan melalui wawancara dan observasi, kemudian dianalisis melalui tiga tahapan, yaitu reduksi data, penyajian data, dan penarikan atau verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa siswa berprestasi cenderung memiliki kebiasaan belajar yang positif, seperti menyusun dan merencanakan jadwal belajar, mengikuti pelajaran secara teratur, mengulang materi, mengelola waktu dengan baik, menjaga fokus, serta menerapkan disiplin saat belajar. Strategi belajar ini dilakukan baik di sekolah maupun di rumah, sehingga membantu siswa dalam mengelola stres akademik dan mempertahankan prestasi yang tinggi. Selain itu, temuan ini diharapkan dapat memotivasi siswa yang kurang berprestasi untuk mengadopsi pola belajar serupa demi meningkatkan hasil akademik dan pengembangan diri. Kata Kunci: disiplin; kebiasaan belajar; pencapaian akademik; pola belajar